Comparison of the Effects of Repeated Applications of Platelet-Rich Plasma versus Platelet-Poor Plasma on Fat Graft Survival in Nude Mice - Li, Junjie (Biomed Res Int, 2021)
Autologous fat grafting has been widely used for soft tissue filling in plastic surgery. Platelet-rich plasma (PRP) could play a wide role in health and disease because of containing a variety of growth factors and cytokines. Although previous studies have described the positive effect of autologous PRP mixed with fat grafts, only minimal improvements in fat graft survival have been reported. The present study is aimed at comparing the effects of PRP and platelet-poor plasma (PPP) on the survival and quality of fat grafting. We built a 180-day nude mouse model implanted with a fat graft supplemented with PRP, PPP, or saline, respectively. The above reagents (PRP, PPP, or saline) were injected two additional times after the initial engraftment. The survival ratio of the fat grafts and the capillary density in the PRP group were significantly higher than those in the PPP group and the saline group (control group) at 15, 30, 90, and 180 days posttransplantation (P < 0.05). The survival ratio of the PPP group was higher than that of the saline group (P < 0.05), but the capillary density in the PPP group was not significantly different from that in the saline group at any time point (P > 0.05). We hence conclude that the repeated application of PRP or PPP three times can enhance the survival of fat grafts within 180 days. Moreover, the effect of PRP is superior to that of PPP.